2010
DOI: 10.1016/j.febslet.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate‐induced translocation of prestin having mutation in the GTSRH sequence to the plasma membrane

Abstract: a b s t r a c tPrestin is a key molecule for mammalian hearing. The present study investigated changes in characteristics of prestin by culturing prestin-transfected cells with salicylate, an antagonist of prestin. As a result, the plasma membrane localization of prestin bearing a mutation in the GTSRH sequence, which normally accumulates in the cytoplasm, was recovered. Moreover, the nonlinear capacitance of the majority of the mutants, which is a signature of prestin activity, was also recovered. Thus, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Collectively, these observations suggest that the R130S mutation impairs membrane targeting, consistent with previous studies suggesting the importance of the R130 region within the prestin molecule for targeting [13, 35]. …”
Section: Resultssupporting
confidence: 90%
“…Collectively, these observations suggest that the R130S mutation impairs membrane targeting, consistent with previous studies suggesting the importance of the R130 region within the prestin molecule for targeting [13, 35]. …”
Section: Resultssupporting
confidence: 90%
“…The nonlinear capacitance change involved in prestin requires some ions such as Cl À and HCO3 À and is inhibited by 10 mM of salicylate (Oliver et al, 2001). Recently, we have reported that salicylate induces the translocation of prestin mutants to the plasma membrane from the cytoplasm (Kumano et al, 2010). There is approximately a 45% similarity between pendrin and prestin in amino acid sequences and transport of anions by pendrin is similar to those transported by prestin (Mount and Romero, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we have reported that salicylate, which binds to prestin with high affinity (Tunstall et al, 1995;Kakehata and Santos-Sacchi, 1996), induces the translocation of prestin mutants to the plasma membrane from the cytoplasm (Kumano et al, 2010). Prestin is a member of the SLC26A gene family including pendrin, and there is approximately a 45% similarity between these proteins in amino acid sequences.…”
Section: Introductionmentioning
confidence: 98%
“…For NLC measurements, cells were examined 24 -48 h after transfection. In one experimental series (C415S), 10 M salicylate was added to the medium to promote translocation to the plasma membrane (Kumano et al 2010). Salicylate blocks prestin NLC, so the salicylate was removed at least 1 h before electrophysiological measures (Kakehata and Santos-Sacchi 1996;Tunstall et al 1995).…”
Section: Methodsmentioning
confidence: 99%